Unusual Internal Electron Transfer in Conjugated Radical Polymers. Issue 33 (19th July 2017) - Li, Fei; Gore, Danielle N; Wang, Shaoyang; Lutkenhaus, Jodie L
Abstract: Nitroxide‐containing organic radical polymers (ORPs) have captured attention for their high power and fast redox kinetics. Yet a major challenge is the polymer's aliphatic backbone, resulting in a low electronic conductivity. Recent attempts that replace the aliphatic backbone with a conjugated one have not met with success. The reason for this is not understood until now. We examine a family of polythiophenes bearing nitroxide radical groups, showing that while both species are electrochemically active, there exists an internal electron transfer mechanism that interferes with stabilization of the polymer's fully oxidized form. This finding directs the future design of conjugated radical polymers in energy storage and electronics, where careful attention to the redox potential of the backbone relative to the organic radical species is needed. Abstract : Conjugated radical polymers : Evidence for the internal transfer of an electron from a nitroxide group to the polythiophene backbone explains the conductivity and redox activity of polythiophenes bearing pendant nitroxide radicals.